The Transmission Spectrum of the Potentially Rocky Planet L 98-59 c - Thomas Barclay; Kyle B. Sheppard; Natasha Latouf; Avi M. Mandell; Elisa V. Quintana; Emily A. Gilbert; Giuliano Liuzzi; Geronimo L. Villanueva; Giada Arney; Jonathan Brande; Knicole D. Colón; Giovanni Covone; et al. (The Astronomical Journal)
We present observations of the 1.35 ± 0.07 Earth radius planet L 98-59 c, collected using Wide Field Camera 3 on the Hubble Space Telescope (HST). L 98-59 is a nearby (10.6 pc), bright ( H = 7.4 mag) M3V star that harbors three small, transiting planets. As one of the closest known transiting multi-planet systems, L 98-59 offers one of the best opportunities to probe and compare the atmospheres of rocky planets that formed in the same stellar environment. We measured the transmission spectrum of L 98-59 c, and the extracted spectrum showed marginal evidence (2.1 σ ) for wavelength-dependent transit depth variations that could indicate the presence of an atmosphere. We forward-modeled possible atmospheric compositions of the planet based on the transmission spectrum. Although L 98-59 was previously thought to be a fairly quiet star, we have seen evidence for stellar activity, and therefore we assessed a scenario where the source of the signal originates with inhomogeneities on the stellar surface. We also see a correlation between transits of L 98-59 c and L 98-59 b collected 12.5 hr apart, which is suggestive (but at <2 σ confidence) of a contaminating component from the star impacting the exoplanet spectrum. While intriguing, our results are inconclusive and additional data are needed to verify any atmospheric signal. Fortunately, additional data have been collected from both the HST and James Webb Space Telescope. Should this result be confirmed with additional data, L 98-59 c would be the first planet smaller than 2 Earth radii with a detected atmosphere.